Holocaust versus Wehrmacht: how Hitler's "Final Solution" undermined the German war effort - Pasher, Yaron (Modern war studies, 2014)
"Pasher argues that a major share of the logistical problems confronting the German army throughout their military campaigns in World War II stemmed from Hitler's obsession with implementing the "Final Solution"--i.e., the forced removal and eradication of Europe's Jews. Pasher persuasively makes the case that the resources for that ideological enterprise clearly undermined the Wehrmacht's efforts to achieve its military objectives"--